Dampak Pertumbuhan Ekonomi, Suku Bunga, Inflasi, dan Kebijakan Fiskal terhadap Investasi di Indonesia - Enggal Sriwardiningsih (Bina Nusantara University, 2010)
Difficulty of finding investment funding has made a nation uses every means to gather them. Sources of investment funding to come from domestic as well as from abroad. Governments should be able to induce foreign investors to be interested in investing in Indonesia, as well as how to make the capital owners in the country to remain willing to make investments in Indonesia so that they do not invest their capital abroad. In this regard, the government must be able to prepare a conducive investment climate in the country (economic growth, interest rates, inflation, and macroeconomic policies in the country) for economic actors to feel safe in their activities. The purpose of this study is to see the impact of domestic capital and foreign capital in investment transactions in Indonesia. The methodology used is regression with time series. The analysis showed that changes in macroeconomic conditions such as growth, interest rates and inflation in some developed countries, including America and European countries in the region does not give a significant influence on Indonesian Foreign Investment, therefore the impact of the severe financial crisis in America and Europe today on Indonesian Foreign Investment is still within limits of tolerance. Therefore, although there are problems in the investment climate in Indonesia, Indonesia's investment prospects over the coming period is still good, though perhaps with slowed investment growth.